Collection, Detection, Assessment, Monitoring and Prevention of Adverse Drug Reactions in the Nephrology Department of Gauhati Medical College and Hospital, Assam, India (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: nephrology; renal dysfunction; moon face; hypersensitivity; hepatotoxicity